ISLAMIC PARENTING IN SANDWICH GENERATION - Dewi, Salamiah Sari; Surbakti, Amanah; Nataya Nasution, Atika Mentari (Psikis : Jurnal Psikologi Islami, 2022)
This study aimed to find out more about Islamic Parenting in Sandwich Generation. The research method used in this research is qualitative research with a case study approach. This research was conducted by collecting observation data and interviews with the parents of the SDN 027962 Binjai students who are the sandwich generation according to the journal of M. Sahal. The selection of the study location was based on interviews from parents of students who complained about their positions as sandwich generation. The study was conducted on 3 parents of students. The data analysis technique was carried out by data reduction, data presentation, and conclusion. The results of this study indicated that the application of Islamic parenting in the sandwich generation has been going quite well. The differences found in implementing Islamic parenting were based on differences in parents' economic conditions, which gave impact to the availability of time and understanding of religion by parents who became the sandwich generation. Parents who had low economic conditions tend to use practical parenting and rely on the involvement of experts (parents or teachers) to cover the lack of time that can be provided to care for their children. The study concluded that efforts to implement Islamic parenting based on M. Sahal’s journal such as al-Mukalatah or socialization, al-I’tiyad or habituation, al-Ta’allum or learning, internalization and integrity, and religious children can be applied to families experiencing the sandwich generation.